Focused ultrasound-triggered chemo-gene therapy with multifunctional nanocomplex for enhancing therapeutic efficacy - Han, Hyounkoo; Kim, Doyeon; Jang, Yongho; Seo, Minkyu; Kim, Kwangmeyung; Lee, Jong Bum; Kim, Hyuncheol (ELSEVIER, 2020)
Nanotechnology-based combination therapies, especially chemo-gene therapy, have been spotlighted as promising alternatives for cancer therapy. However, only a small amount of systemically administered nanomedicines reach the tumor site by the enhanced permeability and retention (EPR) effect, resulting in the limited therapeutic efficacy. Furthermore, the design of ideal drug delivery system for chemo-gene therapy has been impeded by the chemical and physical differences between nucleic acids and chemotherapeutics. Herein, we report a precisely designed nanocomplex which exhibits a focused ultrasound (FU)-responsive release and enhanced accumulation of released therapeutics to tumor site. After the nanocomplex composed of siRNA nanoparticles (siRNA-NP) and chemotherapeutics-loaded microbubbles was systemically injected, the nanocomplex was collapsed around the tumor tissue by FU exposure, and both siRNA-NP and chemotherapeutics were penetrated the dense extracellular matrix (ECM) of tumor site, leading to the enhanced chemo-gene therapeutic efficacy. The two-in-one nanocomplex is expected as a promising platform for combination therapy that can enhance the therapeutic efficiency of combination drugs at the cell and/or tissue levels with high drug loading ratio.
Keywords: SURFACE-PROPERTIES; TUMOR-DIAGNOSIS; BREAST-CANCER; IN-VIVO; SIRNA; PACLITAXEL; DELIVERY; DRUG; NANOPARTICLES; PENETRATION